Innovative use of air-cooled blast furnace slag as a subgrade material for embedded track slabs: In situ and laboratory tests and simulations - Bin-Chen Benson Hsiung; Muhammad Dwiyanto Agung Prakasa (Results in Engineering)
Air-cooled blast furnace slag (ACBFS) is often ground into powder and mixed with concrete or cement mortar to increase the strength of concrete but has not been directly adopted as a subgrade material in railway or tram projects. However, considering its high porosity, low density, and excellent drainage capacity, the potential of ACBFS as a sustainable and effective subgrade material is verified via a comprehensive case study of tram construction projects in Taiwan. The material properties of ACBFS are examined through in situ and laboratory testing, thereby providing insights into its performance, and 3D feedback analysis is employed to determine the elastic modulus. Both 2D and 3D numerical analyses are performed to determine the possible settlement and stress conditions of embedded track slabs induced by full-scale tram operation. The results suggest that the elastic modulus of ACBFS is 400 MPa and that the confining pressure and ageing period determine the material stiffness. Furthermore, ACBFS provides a sustainable and effective subgrade material solution for tramway engineering, with consistent simulation results of settlement and stress patterns under full-scale tram operations. To fulfil the operation requirements, a 30-cm layer of ACBFS subgrade material is needed. Additionally, a comparative study of the performance of ACBFS and other ground improvement materials/methods is provided. The findings show that ACBFS, recognised for its environmentally friendly properties, is also effective in minimising settling under tram loads while necessitating a smaller quantity of material than other improvement alternatives do.